Augmentative Asenapine in a Recurrent Manic Catatonic Patient with Partial Response to Clozapine - Buoli, Massimiliano; Dobrea, Cristina; Caldiroli, Alice; Cremaschi, Laura; Altamura, A. Carlo (Case Reports in Psychiatry, 2013)
Catatonia is a severe but treatable neuropsychiatric syndrome known since the middle of the nineteenth century. It has been considered for a long time as a subtype of schizophrenia, even though this association occurs only in 10% of cases. In contrast, it is frequently observed in bipolar patients. First-line treatment consists of benzodiazepines, while in case of resistance electroconvulsive therapy (ECT) and clozapine have shown positive results. In addition, recent studies reported the efficacy of some atypical antipsychotics. The present case shows the clinical response to augmentative asenapine in a catatonic manic patient with a partial response to clozapine.